2018
DOI: 10.1186/s13018-018-0775-4
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcome and physical activity measured with StepWatch 3™ Activity Monitor after minimally invasive total hip arthroplasty

Abstract: BackgroundSubjective data and physical examinations of patients after total hip arthroplasty are used to assess the outcome. But regarding the physical activity, no objective data can be delivered by existing scores. The level of activity can be measured objectively by counting gait cycles. The aim of this study was to measure activity levels of patients before and after total hip arthroplasty (THA).MethodsForty-six patients were included in this prospective study. Western Ontario and McMaster Universities Art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…In contrast, Höll et al studied 46 patients undergoing MIS-THA and reported that patients significantly improved their number of gait cycles per day at 3 months and 6 months, possibly attributed to the MIS approach. 19 Other studies have also shown increases in physical activity after THA and TKA at 6 months. 24,25 De Groot et al prospectively followed 80 patients with osteoarthritis undergoing TJA and determined that patients experience a small increase in actual physical activity, defined as movement-related activities (for example, walking, cycling), body postures (for example, sitting and standing), and changes in body posture (for example, sit-to-stand movement), after 6 months (7%), albeit not clinically significant.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…In contrast, Höll et al studied 46 patients undergoing MIS-THA and reported that patients significantly improved their number of gait cycles per day at 3 months and 6 months, possibly attributed to the MIS approach. 19 Other studies have also shown increases in physical activity after THA and TKA at 6 months. 24,25 De Groot et al prospectively followed 80 patients with osteoarthritis undergoing TJA and determined that patients experience a small increase in actual physical activity, defined as movement-related activities (for example, walking, cycling), body postures (for example, sitting and standing), and changes in body posture (for example, sit-to-stand movement), after 6 months (7%), albeit not clinically significant.…”
Section: Discussionmentioning
confidence: 93%
“…These findings are well supported by the literature as many studies have reported the lack of correlation between subjective clinical evaluation scores and objective measures in physical activity. 6,16,19,23,25 Patientreported activity via questionnaires has been shown to have poor reliability and demonstrate several validity issues. 11 Therefore, our findings further strengthen previous reports that suggest that subjective clinically reported improvements do not necessarily correlate to increased objective levels of physical activity after THA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite concerns over standardization ( 19 ), studies have shown an association between presurgical values and postoperative outcomes ( 20 22 ). However, discrepancies between PROMs and performance-based function are seen ( 23 ) and a number of studies have suggested caution when only using subjective data as the measure of recovery ( 23 25 ). Additionally, compared with preoperative function, postoperative activity levels are low and many individuals become socially isolated following surgery ( 26 , 27 ).…”
Section: Introductionmentioning
confidence: 99%